2015
DOI: 10.1007/s00464-015-4269-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of incremental distal gastric myotomy lengths on EGJ distensibility during POEM for achalasia

Abstract: Background During peroral esophageal myotomy (POEM) for the treatment of achalasia, the optimal distal gastric myotomy length is unknown. In this study we used a functional lumen imaging probe (FLIP) to intraoperatively measure the effect of variable distal myotomy lengths on esophagogastric junction (EGJ) distensibility. Methods EGJ distensibility index (DI) (minimum cross-sectional area divided by intra-bag pressure) was measured with FLIP after each operative step. Each patient's myotomy was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…33 Intraprocedural application of EndoFLIP to POEM was highly predictive of postoperative symptomatic outcomes. 34,35 Along with the improvement of manometric profiles of EGJ, Figure 3. Endoscopic myotomy of circular muscle bundle begins from 2-3 cm distal to the mucosal entry and extends to 2-3 cm distal to the esophagogastric junction.…”
Section: Short-term Outcomesmentioning
confidence: 90%
“…33 Intraprocedural application of EndoFLIP to POEM was highly predictive of postoperative symptomatic outcomes. 34,35 Along with the improvement of manometric profiles of EGJ, Figure 3. Endoscopic myotomy of circular muscle bundle begins from 2-3 cm distal to the mucosal entry and extends to 2-3 cm distal to the esophagogastric junction.…”
Section: Short-term Outcomesmentioning
confidence: 90%
“…Several studies have demonstrated an immediate increase in EGJ-DI following POEM or Heller myotomy (associated with a slight decrease following fundoplasty creation) 1620 . Further, intra-operative FLIP may provide a method to ‘tailor’ the myotomy +/− fundoplasty to help improve dysphagia (i.e.…”
Section: Achalasiamentioning
confidence: 99%
“…Pandolfino et al indicated that successfully treated achalasia patients had significantly higher EGJ‐DI than untreated patients. Intraoperative distensibility measurement using FLIP was first reported by Perretta et al Subsequent studies further confirmed that the CSA of the EGJ and the LES‐DI significantly increased after a Heller myotomy or POEM . Measuring distensibility with FLIP intraoperatively offers the possibility to assess the efficacy of LES myotomy in real time, which potentially predicts a patient's clinical response to therapy .…”
Section: Flip For Achalasiamentioning
confidence: 94%